Analysis of Effective Drivers on the Implementation of Rural Development Plan and Progress of Rural System Using DPSIR Model; A Case Study: Rural System of Central and Dotapeh Districts in Khodabandeh County - Seyyed amirhosein Garakani; Jafar Mahdioun; Majid Hazrati (مسکن و محیط روستا)
The rural development plan and progress of rural systems are designed to promote sustainable development of rural settlements through spatial organization of rural systems in the form of local and regional networks, emphasizing rural-urban relationships and encouraging local governance through community participation. Additionally, it aims to strengthen the effective social and economic relationships of settlement units within the system. This plan, with a focus on activating the production cycle in rural spaces and creating employment and entrepreneurship opportunities, can facilitate the path to overcoming the crisis of rural development. This article employs a descriptive-analytical method to analyze the effective drivers on the implementation of the rural development plan and progress of rural systems in the central and Dotapeh districts of Khodabandeh County. Data collection was conducted through library and field studies, with a statistical population of 93,939 residents in the Dotapeh and central districts. Due to the specialized nature of the topic, a sample of 30 experts was selected using the snowball sampling method. The TODIM model and the least squares method within the DPSIR model were used for data analysis with the help of Excel and Smart PLS software. The research findings indicate that the "driving force" factor, with a score of 0.637, had a greater impact on the implementation of the rural development plan and progress of the rural systems in the central and Dotapeh districts of Khodabandeh County than other components. Furthermore, in order to achieve a more effective implementation of the rural development plan and progress of the rural systems, the following structures were found to have the greatest impact: P1. Organizing jobs related to the function and capacity of villages and the county (0.809); D2. Support from the Islamic Revolution Housing Foundation (0.782); S1. Attention to cluster economic and production capacities in the zoning of the system (0.778); and P3. The possibility of pursuing violations and laziness through decision-making institutions (provincial and governorate) (0.778). Finally, in order to achieve the goals of the rural development plan and progress of the rural systems, it is necessary to provide credit facilities through monitoring by the facilitation office, hold rural festivals, strengthen direct communication between facilitators and entrepreneurs, strengthen local organizations, and review the services provided by rural system offices.